Visualized study of the flow field and temperature field in the all-glass evacuated solar collector tube - ZHONG Jian-li; FU Li-xia; LEI Jin-bo (浙江大学学报. 农业与生命科学版, 2005)
In this article the FLUENT compute model of all-glass evacuated solar collector tube is constructed according to a physical model and the interface of FLUENT. The boundary conditions are established on the basis of the data of three different states of water stagnation. The calculation results have a good match with the test results. By FLUENT, we can graphically observe the variation in fluid field and temperature field during covered solarization of solar collector tube and obtain the data of heat loss by different ways.